Detection of Ovarian Cancer: Combined Use of CA 125 and Inhibin as Tumor Marker - Dubbewar, Avinash P.; Hiremath, Ravishekar N.; Viswanath, Kasi; Ghodke, Sandhya; Pathak, B.; Biswas, Manas; Malhotra, Gunjan; Gouru, Prathyusha; Yadav, Preeti (Research Highlights in Disease and Health Research Vol. 2, 2023)
The current study compares the efficacy of a combined test using CA 125 and Inhibin for early detection of ovarian cancer to CA125 or Inhibin alone. Fifty women attending Gynae OPD with clinical suspicion of ovarian malignancy were included in the study. Prior to surgery, all of these women had their CA 125 and Inhibin levels measured. The findings showed that Out of 50 patients recruited, 30 (60%) were found to have carcinoma ovary and 20 (40%) were found to have benign diseases. Out of 30 cases of carcinoma ovary, CA125 was raised in 81% of cases and Inhibin was raised in 78% of cases. CA 125 was found to have a sensitivity of 90% and specificity of 60% for detecting carcinoma ovary, with a statistically significant positive predictive value of 77% and negative predictive value of 80%. The sensitivity and specificity of serum Inhibin for the same were 86.6% and 20%, respectively. The positive and negative predictive values were 61.9% and 50%, respectively, and were not statistically significant. The combined CA125 and Inhibin sensitivity and specificity were 100% and 30%, respectively. The positive and negative predictive values were 68.1% and 100%, respectively, and were statically important. In comparison to CA125 or Inhibin used alone, the combination of CA125 and Inhibin has higher sensitivity and specificity in detecting ovarian cancer.